2006
DOI: 10.1128/aac.50.5.1649-1655.2006
|View full text |Cite
|
Sign up to set email alerts
|

New Potential Antimalarial Agents: Therapeutic-Index Evaluation of Pyrroloquinazolinediamine and Its Prodrugs in a Rat Model of Severe Malaria

Abstract: Tetra-acetamide pyrroloquinazolinediamine (PQD-A4) and bis-ethylcarbamyl pyrroloquinazolinediamine (PQD-BE) are new derivatives of pyrroloquinazolinediamine (PQD) and are being investigated as potential chemotherapeutic agents for the treatment of malaria. Comparative studies to assess the therapeutic indices of PQD-A4, PQD-BE, and PQD were conducted in Plasmodium berghei-infected rats following daily intragastric dosing for three consecutive days. Artesunate (AS), a standard drug for treatment of severe malar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…In this study, the decrease of body weight was calculated as a sole index of anorexic toxicity to evaluate the GI toxicity of the PQD drugs in rats ( Table 1). The index results showed that (i) anorexic toxicity was dose dependent for the three PQDs; (ii) GI toxicity was significantly reduced by the derivatives, PQD-A4 and PQD-BE, compared to PQD at any dose level; and (iii) the GI toxicity of PQD was about 3.8-and 8.8-fold higher than those of PQD-BE and PQD-A4, respectively, which had similar safety margins (3.2-and 8.0-fold), as shown in our therapeutic-index study, with the same multiple doses (27).…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…In this study, the decrease of body weight was calculated as a sole index of anorexic toxicity to evaluate the GI toxicity of the PQD drugs in rats ( Table 1). The index results showed that (i) anorexic toxicity was dose dependent for the three PQDs; (ii) GI toxicity was significantly reduced by the derivatives, PQD-A4 and PQD-BE, compared to PQD at any dose level; and (iii) the GI toxicity of PQD was about 3.8-and 8.8-fold higher than those of PQD-BE and PQD-A4, respectively, which had similar safety margins (3.2-and 8.0-fold), as shown in our therapeutic-index study, with the same multiple doses (27).…”
Section: Discussionsupporting
confidence: 57%
“…The two derivatives showed exceptionally less toxicity and higher therapeutic indices than their parent drug, which successfully reduced side effects associated with PQD in our previous study (27) and in the present studies. However, the two derivatives of PQD also reduced the bioavailability by one-half compared to PQD in rats.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Recently, the tetraacetyl prodrug 71 showed markedly superior efficacy and safety in a mouse model of severe malaria relative to artesunate (42). [276] …”
Section: Structurally Different Compoundsmentioning
confidence: 99%